Lung cyst and multinodular thyroid goiter: Keys to DICER1 syndrome diagnosis in a 16‐year‐old female - Tutor, James D. (Clin Case Rep, 2020)
Pulmonary cysts and neoplasms, especially congenital or occurring at a young age, should be thoroughly investigated. Evaluation for DICER1 mutations should be performed if there is a family history of this syndrome, the lung cyst/neoplasm is a pleuropulmonary blastoma, or other clinical manifestations of this syndrome are present or develop.